2008
DOI: 10.4103/0973-3930.43101
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of chronic kidney disease in a Sri Lankan population

Abstract: CONTEXT:Chronic kidney disease (CKD) is characterized by progressive destruction of renal mass with irreversible sclerosis and loss of nephrons over a period of months to years, depending on the underlying etiology.AIM:To describe demographic patterns and identify common causes of CKD in patients admitted to ward 41 and 48B, National Hospital of Sri Lanka.SETTINGS AND DESIGN:A hospital based descriptive 3-month study was conducted at ward 41 and 48B, National Hospital of Sri Lanka. A case record form was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 4 publications
2
55
0
1
Order By: Relevance
“…They reported that CKDu (CKD of unknown etiology) had a point prevalence ranging from 2-16% among those aged >18 years. [7][8][9] and that biopsy primarily showed tubulointerstitial involvement, secondary glomerulosclerosis and glomerular ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that CKDu (CKD of unknown etiology) had a point prevalence ranging from 2-16% among those aged >18 years. [7][8][9] and that biopsy primarily showed tubulointerstitial involvement, secondary glomerulosclerosis and glomerular ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that CKD and genito-urinary related hospital admissions in the country have almost doubled over the past two decades. Concurrently, the in-hospital mortality from CKD has increased to 9.1 from 2.6 per 100,000 population [4]. Some of the reasons for these disappointing results include; lack of adequate state sponsored renal replacement therapy, poor patient acceptance of peritoneal dialysis, relatively low rate of deceased donor organ donation and prohibitive costs of transplant immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO recommendation for optimal blood pressure for follow up of hypertensive patients, states that the values should be 130/90mmHg or below. Uncontrolled blood pressure is a known risk factor for the development of CKD 3 . The results of serum creatinine and cystatin C with the low estimated GFR obtained from this study revealed that many of these patients have developed chronic kidney disease.…”
Section: Disussionmentioning
confidence: 99%
“…Hypertension in blacks is a notable cause of kidney disease and usually progress to end stage renal failure due to late presentation 2 . Lack of proper medical treatment of hypertension can also result in complications like stroke, visual impairment and renal disease 3 . Chronic kidney disease is a known complication of hypertension especially when the blood pressure is uncontrolled 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation